We have f(x) = 5x - 1 and g(x) = 3x^2 + 4. To determine f ◦ g, we substitute g(x) into f(x) and get:
f(g(x)) = 5(3x^2 + 4) - 1
f(g(x)) = 15x^2 + 19
To determine g ◦ f, we substitute f(x) into g(x) and get:
g(f(x)) = (5x - 1)^2 + 1
g(f(x)) = 25x^2 - 10x + 2
We have f(x) = 1 - 3x and g(x) = x^2 + 1. We evaluate f(g(f(0))) as follows:
f(g(f(0))) = f(g(1)) (since f(0) = 1)
f(g(f(0))) = f(2) (since g(1) = 2)
f(g(f(0))) = 1 - 3(2) (since f(2) = -5)
f(g(f(0))) = -14
Therefore, f(g(f(0))) = -14.
(a) We have f(n) = n^2 + 1 and g(n) = 1/n. Then,
(g ◦ f)(n) = g(f(n)) = g(n^2 + 1) = 1/(n^2 + 2)
(b) We have f(x) = 1/(x^2 + 1) and g(x) = 1 - x. Then,
(g ◦ f)(x) = g(f(x)) = g(1/(x^2 + 1)) = 1 - 1/(x^2 + 1)
(c) We have f(x) = 1/(x - 2) and g(x) = 1/x. Then,
(g ◦ f)(x) = g(f(x)) = g(1/(x - 2)) = (x - 2)/x
(d) We have f(x) = x^2 + 1 and g(x) = sqrt(x - 1). Then,
(g ◦ f)(x) = g(f(x)) = sqrt(x^2) = x
(e) We have f(x) = 3x - 7 and g(x) = 2x/(x - 3). Then,
(g ◦ f)(x) = g(f(x)) = 2(3x - 7)/(3x - 10)
Let A = {1, 2}, B = {3, 4}, C = {5, 6}, f: A → B be defined by f(1) = 3, f(2) = 4, and g: B → C be defined by g(3) = g(4) = 5. Then g ◦ f is the function from A to C that maps 1 to 5 and 2 to 5. Both g ◦ f and f are one-to-one, but g is not one-to-one since it maps two elements in B to the same element in C.